Narrativas de professoras formadoras que ensinam matemática em cursos de pedagogia: formação, identidade e tensões no campo da docência e da pesquisa - Santos, Cicero Augusto (2023)
This research pertains to a master's thesis affiliated with the Postgraduate Program in Education (PPGE), within the research line "Science and Mathematics Education" at the Federal University of São Carlos (UFSCar), and it is part of the "MANCALA – Group of Studies and Research in Mathematics Education, Culture, and Teacher Education" (CNPq). The ongoing investigation had the overarching objective of comprehending the constitution of the professional identity of female teachers who teach Mathematics in Pedagogy undergraduate programs, along with their tensions within the fields of teaching and research. To achieve this, after identifying collaborating educators who are graduates of stricto sensu postgraduate programs in the areas of "Education" and "Teaching" in São Paulo state, the narrative interview method proposed by German sociologist Fritz Schütze was adopted as the data production instrument. Thus, in pursuit of the stated objective, narratives of three educators, who are both pedagogues and doctors and have developed their professional identities over the course of their journeys as mathematics educators, were validated. In terms of results, utilizing the six steps proposed by Schütze, the analyses reveal the following outcomes: 1) Impact of Positive Training Experiences on Professional Identity: the trainers demonstrated that positive experiences with teachers in Basic Education were crucial for Mathematics to become their preferred subject. This highlights the influence of interpersonal relationships in the formation of the professional identity of pedagogues and shows the importance of support and encouragement at the beginning of their trajectories; 2) Challenges and Tensions of Insertion in the Field of Mathematics Education: the trainers' narratives revealed challenges and tensions faced when entering the field of Mathematics Education, such as questions about their training and capacity. This result highlights the importance of discussing and overcoming these barriers, from the initial training of teachers; 3) Reflections of Teaching Practice and Career Development for the Constitution of Identity: the challenging experiences faced by teachers in the field of Mathematics Education were fundamental to strengthen their professional identities. This suggests that overcoming obstacles can result in a more solid and authentic identity as mathematics educators, which has implications for the training and professional development of other educators. In summary, the work with narratives contributed, in the specific case of this study, so that these professionals could tell their life stories under the aegis of being a teacher in Higher Education.